Hambatan Penerapan Table Official Pada LIMA Basketball (Indonesian Journal for Physical Education and Sport, 2022)
In basketball matches there are match devices that have the task of helping the game run smoothly. One of the match devices in basketball matches that has an important role is the official table. The purpose of this research is to find out the obstacles of table officers in the implementation of Basketball Central Java Student league matches and Special Region of yogyakarta conference season 7. The research method uses qualitative narrative design. The instruments used are observations, interviews, and documentation. The subjects of this study were desk officers and steering commite on duty at LIMA. Data analysis techniques using data triangulation techniques. Analyze data by collecting data, reducing data, and presenting data, and drawing data conclusions.the results showed that 1) the availability of good tools and have a backup tool in case of errors in the tool;2) there are obstacles on the timer officer to adjust in the match;3) some tools such as scoreboard and buzzer do not have fiba standards;4) the condition of the tool is still good;5) the function of the tool runs well;6) the tool can work in accordance with the procedure of using the tool in FIBA regulations except scoreboard;7) environmental conditions such as spectators and weather can cause during a match;8) the table clerk has not been granted legality or license to serve;9) the conditions before, during, and after the match are in accordance with the rules written in fiba. From the results of the study showed some obstacles from equipment, desk officers and environmental conditions.